Evaluasi dan Rekomendasi Strategi Bisnis pada Divisi LPP-TVRI - Prabowo, Hartiwi; Nurhanka, Pona; Hasanah, Sri Budi Utami Nur (Binus Business Review, 2010)
TVRI represent of the first television station in Indonesia. In this time TVRI not yet able to serve any event enthused by people. In the effort improving returning competitiveness of TVRI station in industrial television sector, needed business strategy which capable to accommodate and anticipate change of technological growth that happened quickly and the economic globalization. Research was done to give suggestion at the development of division and broadcast. The purpose of this research is to evaluate business strategy which have been done and propose business strategy which can improve company competitiveness. Analysis techniques which used were Internal External matrix, SWOT matrix, matrix of Grand Strategy, and QSPM matrix. Result of research by evaluate internal condition of company and analyzing of factor external which related, business strategy which appropriate for LPP TVRI is product development strategy. Expected, LPP TVRI will increase new events that more innovative and creative so that able to become pre-eminent event program for TV beholder/audience.Â